Fanfictions: das plataformas digitais para os livros didáticos - ANA CLAUDIA GAUTO DE SOUSA SOVERNIGO (2022)
This thesis aims to analyze suggestions of activities on the fanfiction discursive genre in textbooks selected by the National Book and Teaching Material Program (PNLD) for elementary school (BRASIL, 2018b) and high school (BRASIL, 2019). Among the indicated collections, we identified that six books presented activities related to fanfictions, of which we selected four of them, based on the following criteria: belonging to different collections and presenting more than one page of activities with the discursive genre fanfic, in order to have a material more consistent for analysis, and describe the stages of text production. Thus, for the analysis, we chose the books: Se liga na língua - leitura, produção de texto e linguagem - 8th grade of elementary school (ORMUNDO; SINISCLACHI, 2018), and for high school, Se Liga nas Linguagens - experimenta dialogar! (ORMUNDO et al., 2020), Identidade em ação: Linguagens e suas tecnologias – Um mundo de linguagens (GUIMARÃES et al., 2020), Ser protagonista Linguagens e suas Tecnologias – Interação Social (POUGY et al., 2020). We sought to verify if the activities contribute to the formation of the reader/author, based on the reading of works that mobilize the virtual communities of fans. It is also the focus of our studies to understand how the experience of reading and producing fanfictions, on digital platforms, can be used at school, so that the act of reading and writing a discursive genre makes sense for students, not limited to mechanical activities in which the only reader is the teacher. We also intended to verify how the use of digital tools is proposed in activities with the discursive genre fanfiction in the analyzed textbooks and if they are valid for the formation of readers/authors, in a way that promotes the production of authorial texts. To this end, the studies by Cosson (2020,2021); Jamison (2017); Jenkins (2010, 2009); Jenkins, Green and Ford (2014); Kalantzis, Cope and Pinheiro (2020); Schneuwly, Dolz and Noverraz (2013); Vargas (2015), among others, support the analysis and intervention proposals. The methodology adopted is bibliographic research and document analysis. The investigation contributes in the field of Portuguese language teaching and learning practices regarding the reading and production of discursive genres from/in the digital universe, considering fanfictions. As a result, we show that the activities in the analyzed textbooks do not focus on the practice of reading fanfic in their original media, and, in some cases, do not present the elements that characterize this discursive genre, in a first contact with the text. We also found that the proposals for textual elaboration are more focused on the production of verbal text, that is, the possibilities that digital information and communication technologies (DICT) offer, with regard to multimodality, are not explored. Despite the problems detected, we consider the activities promising, as they include relatively new digital discursive genres, possibly closer to the students' interests.